1978
DOI: 10.1037/0022-3514.36.12.1456
|View full text |Cite
|
Sign up to set email alerts
|

Crime and punishment in the Army.

Abstract: The relationship between crime and punishment is examined and a dilemma in this relationship is identified. Labeling theory suggests that leaders responsible for enforcing the law respond to the crime they see by increasing punishment, under the assumption that punishment will deter crime, whereas recipients often respond to this punishment with a feeling of injustice, which then incites them to break the law more frequently, resulting in more serious problems on a delayed basis. The operation of this sort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Of these subjects, 32% who participated in the scared-straight program subsequently committed their first offense, compared to only 5% of the controls, z = 1.79, p = .07. 3 Sim-ilarly, Hart (1978) reported that in the Army, the nonjudicious application of punishment served to increase rather than decrease offense rates.…”
Section: Discussionmentioning
confidence: 99%
“…Of these subjects, 32% who participated in the scared-straight program subsequently committed their first offense, compared to only 5% of the controls, z = 1.79, p = .07. 3 Sim-ilarly, Hart (1978) reported that in the Army, the nonjudicious application of punishment served to increase rather than decrease offense rates.…”
Section: Discussionmentioning
confidence: 99%
“…Gibbs, 1978) as evidenced by deterrence proponents is frankly a sad state of affairs for such a development can only lead to an abandonment of further research. This cynical scenario, hopefully, may not come to pass as there are some fruitful avenues for deterrence research (e.g., Erickson & Gibbs, 1979;Hart, 1978) that require further exploration. Nevertheless, quick and easy deterrent solutions are far from evident at the present time.…”
Section: Problems and Prospectsmentioning
confidence: 99%